The description of the causes of young marriage - Ririn Wahyu Hidayati (International Journal of Health Science and Technology, 2022)
Marriage at young age has risks of reproductive health such as premarital pregnancy, anemia, to cervical cancer. Based on WHO data in 2018, there were 16 million young women aged 15-19 years who gave birth (WHO, 2018). Therefore, the researcher intends to know the description of the factors that cause marriage at a young age. This research was conducted semi-qualitatively, the number of participants was 14 pairs of prospective brides and grooms. Sampling technique with total sampling. Data analysis with frequency distribution and open interview. The results obtained that the bride and groom aged 19 years were 100% female and 42.9% male.42.9% of prospective grooms and 100% of women had not worked. The results of in-depth interviews with prospective brides who decided to marry at a young age because they were pregnant outside of marriage. Meanwhile, according to the prospective groom, he decided to get married because he felt he was capable enough to meet his needs, was responsible for his actions and already liked each other. Young marriages occur no longer because of lack of knowledge, but because of premarital pregnancy, inappropriate perceptions of marriage, and economic problems.